EFFICACY OF NEW GENERATION HERBICIDES ON WEED DYNAMICS, NUTRIENT UPTAKE AND YIELD OF BLACKGRAM (VIGNA MUNGO L.) - G. SREEKANTH,; B. SANDHYA RANI,; P. MAHESWARA REDDY,; V. CHANDRIKA,; G. KARUNA SAGAR, (The Journal of Research ANGRAU, 2024)
The field experiment was conducted during rabi, 2022-23 at Wetland Farm of S.V. Agricultural  College, Tirupati, to evaluate theefficacy of new generation herbicides for weed management in  blackgram with nine weed management practices in a randomized block design replicated  thrice.Results revealed that among all the weed management practices at 60 DAS lower density  (8.06 No.m-2) and biomass (6.26 g m-2)of total weeds coupled with higher weed control efficiency  and weed control index(74.67 & 74.50 %) was recorded withpre-emergence application of  diclosulam 20 g ha-1 + 1 HW at 15 DAS, which was followed by PoE application of fluazifop-p-butyl  + fomesafen 222 g ha-1(69.32 & 69.28 %) and PoE application of sodium acifluorfen + clodinafop  propargyl 245 g ha-1(68.46 & 68.62 %). Higher seed yield (971 kg ha-1) of blackgram was noticed  with HW twice at 15 and 30 DAS, which was at par with PoE application of fluazifop-p-butyl + fomesafen 222 g ha-1(957 kg ha-1) and PoE application of sodium acifluorfen + clodinafop propargyl  245 g ha-1(910 kg ha-1).